Принцип відповідальності держави перед особою: досвід України та Німеччини - Задніпряна‐Корінна, Мар'яна Юріївна (My University, 2021)
Стаття присвячена порівняльно-правовому дослідженню принципу відповідальності держави перед людиною в Україні та Німеччині. При проведенні аналізу було використано порівняльно-правовий, структурно-функціональний та системний методи дослідження. Їх використання дозволило всебічно проаналізувати теорію та практику реалізації цього принципу в Україні та Німеччині. У наслідок проведеного дослідження встановлено те, що вказаний принцип не реалізується в Україні повною мірою. Доведено те, що він має комплексну природу, елементами якої є позитивна та ретроспективна відповідальність держави. Конкретизовані напрями подальшого розвитку кожного із названих видів відповідальності держави.Слід зазначити, що лаконічність положень Конституції України не дозволяє повною мірою розкрити зміст принципу відповідальності держави перед особою. Тому Конституційному Суду України доцільно роз’яснити його суть на рівні окремого роз’яснювального акта. Цей принцип має комплексний характер. З одного боку, передбачає відповідальне ставлення держави до виконання своїх функцій, і насамперед, до утвердження та захисту прав і свобод людини (позитивна відповідальність), з іншого – зобов’язує державу: нести відповідальність за незаконні рішення, дії та бездіяльність, що порушують права і свободи громадян (ретроспективна відповідальність). Позитивна відповідальність держави перед людиною має реалізовуватися, насамперед, через служіння держави кожній приватній людині. Першою передумовою такої служби є впровадження в практику концепції «людиноцентризму» як нової ідеології державної служби. The article is devoted to the comparative legal study of the principle of state responsibility to man in Ukraine and Germany.The research used comparative legal, structural-functional and systematic research methods. Their use allowed to comprehensively analyze the theory and practice of implementation of this principle in Ukraine and Germany.The study is based on an in-depth analysis of domestic and German professional literature on the subject of research, as well as an analysis of the legislation of Ukraine and the Federal Republic of Germany and relevant law enforcement practice. As a result of the study, it was stated that the principle of state responsibility to the person, although it was constitutionally enshrined, but did not receive a well-established practice of implementation in Ukraine. The conciseness of the provisions of the Constitution of Ukraine does not allow to fully disclose its content. Therefore, it is expedient for the Constitutional Court of Ukraine to clarify its essence at the level of a separate interpretative act. This principle has a complex nature. On the one hand, it provides for a responsible attitude of the state to the implementation of its functions, and above all, for the establishment and protection of human rights and freedoms (positive responsibility), on the other hand, it obliges the state to be responsible for illegal decisions, actions and omissions, which violate the rights and freedoms of individuals (retrospective liability). The positive responsibility of the state to the person should be realized, first of all, through service of the state to each private person. The first prerequisite for such service is the introduction in practice of the concept of “human-centeredness” as a new ideology of public service. The institution of retrospective responsibility of the state to man must also undergo its consistent devel- opment. First of all, it is a question of further development of norms which are a legal basis of material respon- sibility of the state for illegal decisions, actions or inaction by which rights, freedoms and interests of the private person are broken.
Keywords: кафедра економіки і права; держава; приватна особа; відповідальність; принцип; законодавство; state; private person; responsibility; principle; legislation